Enhancing Critical Speaking Through Task-Based Learning in Madagascar’s Rural Education Context - Narovana, Andriamiarana; Setyarini, Sri; Purnawarman, Pupung; Léa, Norolalao Hanta (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
English is the third most spoken language in Madagascar, after French, the national language, and Malagasy, the native language, yet its teaching in rural schools remains challenging due to limited exposure, insufficiently trained teachers, and curriculum constraints. This study focuses on investigating the contribution of the task-based approach to learners’ development of critical speaking, as it helps them use language critically in their everyday lives and enhances their communicative competence. This study also explores the challenges learners face in class that limit their critical speaking development. Utilizing a qualitative approach, data were collected through semi-structured online interviews with two English teachers from junior and senior high schools. The findings reveal that learners from senior high school have improved their speaking skills and critical expression through a task-based approach (role play, debates). In contrast, those from junior high school are still taught through a teacher-centered approach, as they are beginner-level students with limited prior exposure to English; thus, their critical ability is still low. The most significant challenges encountered while developing critical skills are learners’ difficulty in mastering the language itself and the curriculum's extensive content, which must be taught and mastered within a short timeframe. These results highlight the need for curriculum reform that prioritizes communicative tasks, scaffolding at lower levels, and increased instructional time for English. This study contributes to a deeper understanding of classroom practice in rural areas of Madagascar by exploring strategies that foster learners' communicative and critical skills within an English as a Foreign Language setting.